Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis